Tackle characteristics that may increase the likelihood of a successful tackle in rugby union - Hendricks, S.; Matthews, B.; Rhode, B.; Lambert, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The tackle in rugby union is a dynamic and high impact contact situation that occurs frequently during matches and exposes players to high risk of injury and muscle damage. Given the nature and frequency of the tackle situation, tackle contact skills are a prerequisite for participation in rugby union. Most techniques described in training manuals and injury prevention programs are based on anecdotal evidence. Retrospective analysis of the tackle has characterized common injury mechanisms for both the ball-carrier and tackler, and effective ball-carrying techniques. In spite of this, no retrospective analysis from a tackler perspective and its association with successful tackle outcomes in rugby union has been investigated to date. Aim: The purpose of this study is to identify tackler characteristics that may increase the likelihood of a successful tackle outcome in rugby union. Methods Two-thousand and ninety-two tackles from 18 matches of the 2010 Super 14 were analysed. Tackles were coded using characteristics and definitions described in previous research, and characteristics and definitions developed specifically for this study. Characteristics were divided into the three tackles phases i.e. precontact (0.5s preceding contact), contact and post contact. The outcomes of the contact event were divided into tackle outcom, possession, territorial change and result. Multinomial logistic regression was used to determine which tackler characteristics increased the likelihood of a successful outcome. Results: Pre contact: Tracking decreased the tacklers` chances of a successful tackle (Relative Risk Ratio (RRR) 2.24, 95% CI 1.72-2.92, p<0.001) relative to an up and forward head position. Contact: Arm tackles (RRR 2.32, 95% CI 1.62-3.32, p<0.001), collision tackles (RRR 4.98, 95% CI 2.17-11.42, p<0.001) and jersey tackles (RRR 2.56, 95% CI 1.87-3.49, p<0.001), significantly reduced the chances of a successful result relative to shoulder tackles. Post-tackle: A moderate (RRR 0.36, 95% CI 0.26-0.50, p<0.001) or strong (RRR 0.39, 95% CI 0.11-1.35) leg drive by the tackler after contact increased the likelihood of a successful tackle. Using the arms for either pulling (RRR 0.30, 95% CI 0.21-0.43, p<0.001) or wrapping (RRR 0.19, 95% CI 0.13-0.27, p<0.001), improved tacklers` probability for success in contact. Discussion: The characteristics identified in this study are comparable to most training manuals and injury prevention programs. Nonetheless, key characteristics that may require more attention than other characteristics have been identified. The authors of this study propose that coaches and players focus on these key characteristics in training to improve their tackle ability in matches.